2014
DOI: 10.1136/bmj.g3284
|View full text |Cite
|
Sign up to set email alerts
|

Relation between surgeon volume and risk of complications after total hip arthroplasty: propensity score matched cohort study

Abstract: Objectives To identify a cut point in annual surgeon volume associated with increased risk of complications after primary elective total hip arthroplasty and to quantify any risk identified.Design Propensity score matched cohort study. Setting Ontario, CanadaParticipants 37 881 people who received their first primary total hip arthroplasty during 2002-09 and were followed for at least two years after their surgery.Main outcome measure The rates of various surgical complications within 90 days (venous thromboem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
168
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(178 citation statements)
references
References 82 publications
5
168
2
3
Order By: Relevance
“…49 Sample and found that lower complication and mortality rates were associated with high hospital and surgeon volume and that the decrease in complications was more substantial with high surgeon volume than with high hospital volume. It is conceivable that experienced surgeons have been in practice longer and, therefore, have higher surgical volume.…”
Section: Discussionmentioning
confidence: 97%
“…49 Sample and found that lower complication and mortality rates were associated with high hospital and surgeon volume and that the decrease in complications was more substantial with high surgeon volume than with high hospital volume. It is conceivable that experienced surgeons have been in practice longer and, therefore, have higher surgical volume.…”
Section: Discussionmentioning
confidence: 97%
“…Some of the variables that have been shown to affect the outcome after total joint replacement include social and demographic characteristics, medical comorbidities, and surgical technique [3][4][5][6][7]. Areas of continued active research include the effect of intrinsic factors such as obesity [8][9][10], cardiovascular disease [11,12], mental health disorders [13•, 14-17•, 18•, 19], hepatic disease [20, 21•, 22, 23•, 24], nutritional deficiencies [25-29•, 30], bone metabolic disease [31][32][33][34][35][36][37], and diabetes mellitus [38•, 39, 40], as well as external factors such as nicotine use [41,42], recent corticosteroid injections [43][44][45][46][47], and discharge disposition [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Tables showing the patient background data and distribution of laparoscopic time were constructed. Second, the relationship between interval days and laparoscopic time was illustrated by adopting a method for restricted cubic spline curves, as a technique that allows flexible descriptions of non-linear relationships among variables [5,6] . Finally, multivariable linear regression analyses for laparoscopic time were performed with interval days and other adjusting variables including age, gender, comorbidity (in the form of the Charlson comorbidity index [7] ), oncological stage (according to the International Union Against Cancer [8] ), type of surgery (nephrectomy or nephroureterectomy), hospital academic status, and hospital volume.…”
Section: Resultsmentioning
confidence: 99%